Application of multi-frequency power ultrasound in selected food processing using large-scale reactors: A review - Baoguo Xu (Elsevier, 2021)
Ultrasound as an eco-friendly green technology has been widely studied in food processing. Nevertheless, there is a lack of publications regarding the application of ultrasound in food processing using large-scale reactors. In this paper, the mechanisms and the devices of multi-frequency power ultrasound (MFPU) are described. Moreover, the MFPU applied in enzymolysis of protein, and washing of fruits and vegetables are reviewed. The application of MFPU can improve the enzymolysis of protein through modification on enzyme, modification on substrate materials, and facilitation of the enzymatic hydrolysis process. The ultrasound treatment can enhance the removal of microorganisms, and pesticides on the surface of fruits and vegetables. Furthermore, the reactors of ultrasound-assisted enzymolysis of protein, and washing of fruits and vegetables on the industrial scale are also detailed. This review paper also considers future trends, limitations, drawbacks, and developments of ultrasound application in enzymolysis and washing.